Not iodine alone. Role of selenium, zinc, vitamins A, C, E in the physiology and pathology of the thyroid gland - Dmitry I. Trukhan; Inna V. Druk; Inna A. Viktorova (LLC "MEDIAFORMAT", 2024)
Diseases of the thyroid gland occupy one of the central places in clinical endocrinology. The main components for the synthesis of thyroid hormones are iodine and the amino acid tyrosine. Studies conducted in the 21st century indicate a certain effect on the metabolism and function of the thyroid gland and other microelements and vitamins. We searched the PubMed and Scopus information databases for publications devoted to the study of the influence of trace elements selenium, zinc, vitamins A, C, E on the physiology and pathology of the thyroid gland, including sources up to 29.02.2024. Adequate intake of selenium, zinc, along with two other important microelements (iodine and iron), as well as vitamins A, C, E, contributes to normal metabolism of the thyroid gland. Maintaining a physiological balance of micronutrients and vitamins through a sensible diet or taking nutraceuticals is essential to preventing thyroid disease and maintaining overall health. Basal analysis of microelements and vitamins seems appropriate for better selection of patients in need of replacement therapy using nutraceuticals